India - Buckley, A. M., 1968- (Edina, Minn. : ABDO Pub. Co., 2012)
The people, culture, politics, geography, and environment of an ancient land which has been undergoing rapid-fire change.
A visit to India -- Geography : a land of variety -- Animals and nature : rich biodiversity -- History : an epic past -- People : diverse yet united -- Culture : a colorful nation -- Politics : a plural democracy -- Economics : a new superpower? -- India today.
Includes bibliographical references (p. 136-137) and index.
Keywords: India -- Juvenile literature; India